A bright green tag for RNA imaging - Sathyan, Dhrisya; Sünbül, Murat (Nature chemical biology, 2024)
To understand the complex dynamics and diverse functions of RNA, robust technologies for labeling and imaging RNA are highly desirable. A newly developed green fluorescent aptamer named Okra enables the imaging of mRNA dynamics in living cells.